Factors affecting employee turnover in an electronic company in Kuching - Bong, Vui Poh (Universiti Malaysia Sarawak (UNIMAS), 2002)
Many surveys say that the number one issue facing business is finding and keeping employees. Employee turnover has become a global problem in many countries. This study examines three antecedents of turnover intention, which are demographic (age, tenure, marital status, education level, employee status and gender), controllable factors (job satisfaction, organizational commitment, distributive justice, procedural justice, career and self-development, and stress), and uncontrollable factor (perceived alternative employment opportunity). The data was collected from an electronic company in Kuching using questionnaire. Multiple regression analysis was conducted to examine the relationship between independent variable and dependent variable using SPSS WINIO.0. The results show that employee turnover intention is significantly affected by age, tenure, marital status, job satisfaction, procedural justice, stress and perceived alternative employment opportunities. In evaluating the estimated model, the independence variables were found to meet the assumption of normality, linearity and homoscedasticity. Tolerance and Pearson Correlation conducted show that multi-collinearity is not a problem in this study. Further hierarchical regression analysis showed that the extent of controllable factors was much greater than uncontrollable factor on employee turnover intention. Thus, the findings suggest that employee turnover problem in this electronic company can be controlled by improving the management practices.